Toxicity of some Commonly Used Insecticides against Spilarctia Obliqua (walker) - Kumar, Arvind; Bhatnagar, Shiwani; Sharma, R. K. (Indian Forester, 2013)
Deltamethrin was found to be most toxic against the larvae of Spilarctia obliqua followed by triazophos, spinosad, chlorpyrifos and fipronil in leaf dip. LC50 of deltamethrin at 12, 24 and 48 hours after treatment (HAT) was 0.008, 0.0001 and 0.00002 per cent respectively through larval dip method. With leaf dip method the LC50 was 0.007, 0.0002 and 0.00002 at 12, 24 and 48 HAT respectively. Being the novel mode of action and safety point of view spinosad was the most promising insecticide which gave the satisfactory control with safety measures, application and environment.